Profil Kondisi Fisik Atlet Futsal Maimo Fc Kota Sorong - Anwar, Saiful; Amber, Alyandi; Sukowati, Anton (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
This study is intended to determine the physical condition of Maimo FC futsal athletes in Sorong City. This research is a quantitative descriptive research. The subjects of this research were 20 Maimo FC futsal players in Sorong City. In this study, samples were taken using a total sampling technique. The series of data collection was carried out using 4 instruments for each physical condition, namely: 1). Leg Muscle Strength Test (Standing Broad Jump) 2). Speed ​​test (20 yard sprint) 3). Agility test (Shutle run) 4. Aerobic endurance test (Bleep Test). Based on the results of the physical condition test for the Maimo FC Team in Sorong City, it shows that the average results of the leg muscle strength test were 77.23